An awareness program on dengue fever among adults residing in an urban slum area, Coimbatore - G., Sugunadevi; A., Dharmaraj (International Journal of Research in Medical Sciences, 2017)
Background: Dengue fever is a mosquito borne disease transmitted by the Aedes mosquito. This disease is known to be worldwide problem, affecting the tropical and sub-tropical regions. One third of the world’s population is at risk of transmission of disease. So, creating awareness is an effective way of preventing Dengue Fever. The objective of the study was to create awareness on Dengue Fever among adults residing in an Urban Slum area in Coimbatore. Methods: The study was conducted among 150 adults residing in an urban slum area in Coimbatore. After informed consent, pre-test questionnaire was administered to assess their awareness on Dengue Fever. Health education programme was conducted and after one month their improvement in the knowledge on dengue fever was recorded using post-test questionnaire. Results: After the awareness program the improvement in knowledge on Dengue Fever among the study participants was assessed and found to have improved significantly (p< 0.001). Conclusions: Health education on Awareness of Dengue Fever among adults aged 20 to 30 years in urban slum at Coimbatore has produced an improvement in knowledge by 48 percent.